Modelling of Ontology-based Service Compositions using Petri Net - Xia, Yunni; Zhang, Xiang; Luo, Xin; Zhu, Qingsheng (Elektronika ir Elektrotechnika, 2013)
OWL-S, one of the most significant Semantic web service ontologies , provides Web Service providers with a core ontological framework and guidelines for describing the properties and capabilities of their web Services in unambiguous, computer interpretable form. In this work we present a translation-based approach for modelling the semantic Web services described in the OWL-S language. This approach employs Petri net as the fundamental means of modelling and defines a set of translation rules to map OWL-S elements into equivalent Petri net representations. They capture the main aspect of service invocations and the control flow of the service model. A case study based on a real-world OWL-S example is also conducted to examine the effectiveness of the translation-based model. DOI: http://dx.doi.org/10.5755/j01.eee.19.2.3474